Arqueologia e pré-história platina na margem esquerda do Médio Uruguai: Uruguaiana - Gomes, Flamarion Freire da Fontoura (2002)
Where today is Uruguaiana town, in the west boundary Rio Grande do Sul, archaeological researches were developed through the 1960´s, 1970´s. Part of the result of these researches indicated that the human presence in the region retraced to a period of time much previous to the European arrival (century XVI XVII). Since this check, there were developed a series of studies, which are characterized by the inconstancy of the interpretations about the archaeological material, coming from the region. Great part of these studies were fixed exhaustively in the technotipologie analyses of the material, what contributes to a series of questioning that did not explained themselves just through artifacts studied isolated. Observations related to inappropriate naming, questioning field methods, few publications and simple interpretations created a panorama of intense debate about the PreHistory of Rio Grande do Sul, particularly about this region. In the aim to orient new researches about the PreHistory of the west boundary, it was realized a bibliographic survey about the issue, taking since the more traditional views, well with the position of the specialized critic. The developed themes in this work come from considerations apt to the environmental alterations, the material culture of the most antique hunter-seekers to the arrival of the holticulture producers. This work finishes winth the exposition of basic elements of archaeological research, thinking about the methods, techniques and theoretical focus, so as to subsidize the reader about the practices that can be adequate to the works and the research context of the researches about Archaeology done up o this moment.